Profitability of Islamic Banks in Indonesia: Evidence From IC, BOPO, and Islamicity Index - Alvito Rido; Bima Cinintya Pratama; Hadi Pramono; Nur Isna Inayati (Fakultas Ekonomi, Universitas Muslim Indonesia, 2026)
This study analyzes the influence of Intellectual Capital, operational efficiency, and the Islamicity Performance Index (IPI) on the profitability of Islamic Commercial Banks in Indonesia during 2021–2024. Using a quantitative approach, this study examined 52 research samples derived from 13 Islamic banks based on annual report data. Intellectual Capital was measured using the iBVAIC model; operational efficiency was proxied by BOPO; Islamicity Performance Index was represented by PSR, ZPR, EDR, and IIR; and profitability was measured using ROA. Panel data regression with a Random Effects model and robust standard errors was employed for data analysis. The findings show that Human Capital and Structural Capital positively affect ROA, while Physical Capital is insignificant. Both operational efficiency and the Islamicity Performance Index have a significant negative effect on profitability. Overall, the findings indicate that the examined variables collectively provide a strong explanatory power for variations in ROA, underscoring the importance of strengthening human resource quality, improving cost efficiency, and optimizing sharia compliance to enhance the sustainable performance of Islamic banking. This study provides both theoretical reinforcement and practical guidance by highlighting the strategic roles of intellectual capital, operational efficiency, and the Islamic Performance Index in supporting the sustainable profitability of Islamic banks.